INTERRELIGIOUS DIALOGUE TO THE RECOGNITION OF RELIGIONS: AN ANALYSIS OF HABIB JA'FAR AL HADAR INTERRELIGIOUS DIALOGUE ON LOG-IN CONTENT - Riza Muhammad; Imronudin; Muhammad Hirzy Haikal (Penamas, 2024)
Continuous concerns about intolerance among religious communities have given rise to new models of dialogue facilitated by religious communities on social media. Habib Ja'far al Hadar and Onadio Leonardo are unique and contemporary representations of the commitment to interreligious dialogue on social media for peace between religious communities. This research is qualitative, descriptive-exploratory. The data source for this study was obtained through the Log-in podcast content, while secondary data was taken from books, journals, and media related to interreligious dialogue. Data collection techniques are divided into Observation and Documentation. Data analysis techniques include data reduction and presentation using a pluralism approach. Log-in discussions between religious communities are comedic, honest, open, and enthusiastic about learning from different people without demanding absolute truth and not patronizing each other. The model of interreligious dialogue practiced in the Log-In Podcast is love dialogue. The term Love Dialogue is an exploratory meaning of several podcast episodes. It is taken from Habib Ja'far's sect of love, which has the principles of compassion and brotherhood in humanity. Interreligious dialogue shifts to religious recognition because of the same vision and mission.